Postharvest quality of yam (Dioscorea alata L.) in Costa Rica: Factors that affect during curing and tuber storage - Ramírez-Sánchez, Maricruz (2024)
Introduction. The yam is an important crop in several regions of Costa Rica. However, postharvest losses are high and not quantified. Objective. This study was conducted to determine the causes of quality deterioration and postharvest losses in yam producing areas located in the provinces of Alajuela, Heredia, and Limón. Materials and methods. The quality of the tubers was determined at two postharvest stages: 1) during the curing stage (15 to 30 days at 25-30°C and 85% RH) and 2) at the end of the market shipping simulation (16°C and 85% RH for 28 days). The following quality variables were measured in both stages: weight, length, number of impacts per tuber, number of open or closed striae per tuber, incidence of surface and cut mold, external rot, and incidence of nematode rot. Results. At the end of curing, the presence of open striae was significant in some areas (30% incidence in San Carlos), the presence of surface and cutting mold at harvest (up to 21% incidence of both factors in Upala), nematode damage (35% incidence in Pococí), along with size variations (length, width, and weight) were important factors contributing to losses. At the end of the transportation simulation, the presence of nematode damage (up to 35% incidence), surface mold (15% incidence), cutting mold (up to 49% incidence), and external rot (up to 5% incidence) were significant causes of losses. Conclusion. The results suggest that in the region of the study, a comprehensive review of cultivation and postharvest practices is necessary in order to reduce the factors causing the identified quality defects.